OC-002 Selective Alpha V Integrin Deletion Identifies a Core, Targetable Molecular Pathway that Regulates Fibrosis Across Solid Organs. (4th June 2013) - Henderson, N; Arnold, T; Katamura, Y; Giacomini, M; Rodriguez, J; McCarty, J; Ruminski, P; Griggs, D; Maher, J; Iredale, J; Lacy-Hulbert, A; Adams, R; et al.
Abstract : Introduction: Myofibroblasts are the major source of extracellular matrix components that accumulate during tissue fibrosis, and hepatic stellate cells (HSCs) are the major source of myofibroblasts in the liver. To date, robust systems to genetically manipulate these cells have not existed. The paucity of tools that allow reliable, specific inactivation of genes in myofibroblasts in vivo has greatly hindered progress in understanding the underlying biology of fibrotic diseases. Methods: Mouse models of organ fibrosis: Chronic carbon tetrachloride injection (liver fibrosis), intratracheal bleomycin instillation (lung fibrosis) and unilateral ureteric obstruction (kidney fibrosis). Fluorescent reporter mice: mTmG (Td tomato/EGFP) and Ai14 (Rosa-CAG-LSL-tdTomato-WPRE) mice were crossed with PDGFR β (platelet derived growth factor beta) -Cre mice. Integrin knockout mice: Itgav flox/flox, itgb8 flox/flox and Itgb6 -/- mice were maintained on C57BL/6 background and i tgb3 -/- and Itgb5 -/- mice were maintained on a 129/svJae background. Fluorescent cell sorting: Td Tomato positive cells from Ai14; PDGFR β-Cre mice were sorted using a FACSAria. Results: We report that PDGFR β (platelet derived growth factor receptor beta) Cre inactivates genes in murine HSCs with high efficiency. We used this system to delete the integrin αv subunit because of the suggested role of multiple αv integrins as central mediators of fibrosis in multiple organs. Deletion of the αv integrin subunit in HSCs protected mice from CCl4-induced hepatic fibrosis, whereas global loss of αvβ3, αvβ5 or αvβ6 or conditional loss of αvβ8 on HSCs did not. PDGFR β-Cre effectively targeted myofibroblasts in multiple organs, and deletion of αv integrins using this system was also protective in bleomycin-induced pulmonary fibrosis and renal fibrosis induced by unilateral ureteric obstruction. Critically, pharmacological blockade of αv integrins by a novel small molecule (CWHM 12) attenuated both liver and lung fibrosis, even when administered after fibrosis was established. Conclusion: These data identify a core cellular and molecular pathway that regulates fibrosis, and suggest that pharmacological targeting of all αv integrins may have clinical utility in the treatment of patients with a broad range of fibrotic diseases. Disclosure of Interest: N. Henderson: None Declared, T. Arnold: None Declared, Y. Katamura: None Declared, M. Giacomini: None Declared, J. Rodriguez: None Declared, J. McCarty: None Declared, P. Ruminski Shareholder of: Antegrin Therapeutics, LLC., D. Griggs Shareholder of: Antegrin Therapeutics, LLC., J. Maher: None Declared, J. Iredale: None Declared, A. Lacy-Hulbert: None Declared, R. Adams: None Declared, D. Sheppard: None Declared.